Complexity of Free Trade Agreements (FTAs): a key issue in Malaysian trade policy - Nawawi, Wan Khatina (Khazanah Nasional, 2010)
In an earlier era, entrepot trade was an important component of Malaya's economy. Modern Malaysia's open economy and liberal trading policies ensure that international trade will continue to be a significant platform for economic growth.